PENGGUNAAN VISUALISASI GRAPH DALAM PEMBELAJARAN LUAS INTEGRAL - Memolo, Tundung (Universitas Muhammadiyah Semarang, 2018)
Teachers competence in a variety of representations are needed when students ask then the teacher explains the solution alternative with theappropriate representation. One form of visualization representation ofintegral learning is the Graph described in cartesius diagram. Visualization with Graph can be a solution for students and teachers when learning extensively integral material. The purpose of this study discusses the tutorial of Graph usage briefly in calculation or broad integral visualization. The research method used is applied research. The results showed that Graph is one of the most useful software in visualization and wide calculation in integral material. Among them depict straight lines, curves, a combination of straight lines and curves, combined two curves, and trigonometric functions. Simulation of visualization in Graph can be done accurately and quickly. However, special skills are required in providing input to the function, determining where the shaded area is in the visualization, as well as calculating the shaded area.Keywords: graph, integral, interpretasi, visualisasi